A holistic framework for interpreting positive clinical outcomes in biotechnology - Varma, Nikil (Eastern Journal of Medical Sciences, 2023)
Clinical trials conducted by biotechnology companies are vital to not only the success of their products, but the health and safety of future patients. However, positive study results do not always lead to FDA authorization and subsequent release to the market for numerous reasons including, false positive rates, validity and reliability of outcomes, the significance of results, and the semantics of company communications. Driven by the need to compete within the marketplace, biotechnology companies have motivation to distort and/or present results to make them appear more favorable. As a result, it is important to approach positive clinical trial results with a healthy amount of skepticism and utilize a more holistic approach to evaluating results and determining whether the advertised product should be released into the market.